2020
DOI: 10.3989/scimar.04852.14a
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale distribution of a deep-sea megafauna community along Mediterranean trawlable grounds

Abstract: The large-scale distribution pattern of megafauna communities along the Mediterranean middle slope was explored. The study was conducted between 500 and 800 m depth where deep-water fishery occurs. Although community studies carried out deeper than 500 m are partly available for some geographic areas, few large-scale comparative studies have been carried out. Within the framework of the MEDITS survey programme, we compared the megafauna community structure in ten geographical sub-areas (GSAs) along the Mediter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Regarding the deepest assemblages, differences were detected between those of the northern Alboran Sea and others parts of the Mediterranean and adjacent Atlantic water. The dominant species in the deepest assemblage (MS) of the present study were mostly different from those of the central and eastern Mediterranean Sea, where A. antennatus, N. norvegicus, Aristaeomorpha foliacea and P. martia are dominant (Fanelli et al 2007, Deval et al 2017, Fernandez-Arcaya et al 2019. This fact contributes to the faunistic differentiation of the Alboran Sea, which is important for fisheries management.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Regarding the deepest assemblages, differences were detected between those of the northern Alboran Sea and others parts of the Mediterranean and adjacent Atlantic water. The dominant species in the deepest assemblage (MS) of the present study were mostly different from those of the central and eastern Mediterranean Sea, where A. antennatus, N. norvegicus, Aristaeomorpha foliacea and P. martia are dominant (Fanelli et al 2007, Deval et al 2017, Fernandez-Arcaya et al 2019. This fact contributes to the faunistic differentiation of the Alboran Sea, which is important for fisheries management.…”
Section: Discussionmentioning
confidence: 50%
“…Finally, a higher abundance of A. antennatus was detected in the MS assemblages of the Alboran Island and Gulf of Vera, probably because of the greater presence of submarine canyons in both sectors, which are a preferred habitat for this species (Martínez-Baños 1997). In fact, the presence of populations of A. antennatus attracts a large deep-water trawling fishery to Alboran Island, the northeastern part of the Alboran Sea and the Gulf of Vera (Sardà et al 2004;García-Rodríguez 2003, Fernandez-Arcaya et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Any of these factors is potentially able to bias our perception and knowledge of the geographical distribution of this species. Although the occurrence of S. rostratus is generally known off Sicilian coasts (Tortonese 1956;Ragonese et al 2013), the species was never reported in various experimental bottom trawl surveys performed in the Sicily Channel during the period 1994-2020 (Scacco et al 2002;Relini et al 2010;Ragonese et al 2013;Geraci et al 2017;Fernandez-Arcaya et al 2019;Ragonese 2022; Farrugio and Soldo unpublished * ). Consequently, the findings of S. rostratus documented here are of huge importance, not only because they determine the presence of this uncommon shark in the northern sectors of the Strait of Sicily, but also because they could indicate the presence of a likely spawning area for the species.…”
Section: Discussionmentioning
confidence: 99%
“…The large-scale distribution pattern of megafauna communities along the Mediterranean trawlable middle slope (Fernandez-Arcaya et al, 2019) as well as the large spatio-temporal patterns of demersal fish assemblages in the northern Mediterranean (Meŕigot et al, 2019) were recently explored, but no detailed information and high-spatial resolution were reported for the Ionian basin. A previous study around the Maltese island (Central Mediterranean) suggests that part of the faunal assemblages cannot be considered independently, and that benthic and demersal species are strictly linked in the structuring of demersal communities (Terribile et al, 2016).…”
Section: Introductionmentioning
confidence: 99%